Information Literacy, Digital Library Technology Innovation, and Virtual Community Engagement on Gen Z's Digital Reading Intention: Collaborative Learning Culture as a Mediating Variable - Evi Sulistiyani; Nuphanudin; Amrozi Khamidi; Andi Kristanto; Mohammad Syahidul Haq (Universitas Pendidikan Ganesha, 2025)
Digital transformation has changed the reading behavior of Generation Z, but the level of active engagement with digital libraries remains suboptimal despite the availability of technological infrastructure. This study aims to analyze the influence of information literacy skills, digital library technology innovation, and virtual community involvement on Generation Z's digital reading intentions through collaborative learning culture as a mediating variable. This explanatory quantitative study involved 300 students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that information literacy skills significantly influenced collaborative learning culture and digital reading intentions. Library technology innovation and virtual community involvement significantly influenced collaborative learning culture, but did not directly influence digital reading intentions. Collaborative learning culture was proven to mediate the relationship between the three independent variables and digital reading intentions. This study emphasizes the importance of integrating literacy development, technological innovation, and virtual community building in digital library strategies. The implication is that increasing Generation Z's digital reading intentions is not only influenced by information literacy and digital library technology innovation, but also heavily dependent on the formation of a collaborative learning culture.